PENGARUH MODEL PEMBELAJARAN KOLABORATIF BERBASIS MASALAH TERHADAP KREATIVITAS BELAJAR SISWA KELAS IX SMP IT AL-FITYAH PEKANBARU - Aprilliani, Yusella; Supentri, Supentri; Primahardani, Indra (Komunitas Manajemen Kompetitif, 2024)
Abstract This research is motivated by a phenomenon that occurs in the field, namely at Al-Fityah IT Middle School Pekanbaru. Based on observations made, there is a lack of maximum implementation in the learning model, learning only focuses on the material presented by the teacher, and the learning model is still conventional. This research is a quantitative research experimental design formulating the problem of associative causal relationships. The population in this study was all 41 students in class IX of SMP IT Al-Fityah Pekanbaru. The sample size in this study was 41 students with the data collection techniques used were observation, questionnaires, and documentation, data processing was carried out using IBM SPSS Version 16. Analysis of this research used the normality test, homogeneity test, t test, and n-gain test. score. The results of the t test show that tcount > ttable or 3.344 > 1.685, so it can be concluded that there is an influence of the Problem-Based Collaborative Learning Model on Student Learning Creativity. With an achievement of 69.33% in the experimental class and 40.47% in the control class. Keywords :